2009
DOI: 10.1124/jpet.109.156406
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Diaryl Oxazole-Based Compounds as Potential Agents to Treat Pancreatic Cancer

Abstract: A series of diaryl-and fluorenone-based analogs of the lead compound UA-62784 [4-(5-(4-methoxyphenyl)oxazol-2-yl)-9H-fluoren-9-one] was synthesized with the intention of improving upon the selective cytotoxicity of UA-62784 against human pancreatic cancer cell lines with a deletion of the tumor suppressor gene deleted in pancreas cancer locus 4 (DPC-4, SMAD-4). Over 80 analogs were synthesized and tested for antitumor activity against pancreatic cancer (PC) cell lines (the PC series). Despite a structural rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…However, a subsequent study demonstrated that this compound does not exert its cellular activity by inhibiting CENP-E and rather binds microtubules tightly [461,462]. Another study that tested the antitumor activity of UA62784 and 80 analogs against pancreatic cancer cell lines revealed that these compounds potently inhibit several protein kinases that are overexpressed in these cancer cells, but not mitotic Kinesins (Kinesin-5, CENP-E, MKLP-1, and MCAK) [463]. Another compound, Syntelin, was also reported to be a highly selective CENP-E inhibitor [464].…”
Section: Targeting Chromosome Congression For Cancer Therapymentioning
confidence: 99%
“…However, a subsequent study demonstrated that this compound does not exert its cellular activity by inhibiting CENP-E and rather binds microtubules tightly [461,462]. Another study that tested the antitumor activity of UA62784 and 80 analogs against pancreatic cancer cell lines revealed that these compounds potently inhibit several protein kinases that are overexpressed in these cancer cells, but not mitotic Kinesins (Kinesin-5, CENP-E, MKLP-1, and MCAK) [463]. Another compound, Syntelin, was also reported to be a highly selective CENP-E inhibitor [464].…”
Section: Targeting Chromosome Congression For Cancer Therapymentioning
confidence: 99%
“…The synthesis of PC-046 is reported elsewhere [3]. For in vitro studies, PC-046 stock is prepared in DMSO and subsequently diluted into aqueous media at a final working concentration of less than 0.1% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacokinetics of a single 100 mg/kg dose of PC-046 in non-tumor bearing SCID mice was analyzed by reversed phase chromatography and tandem mass spectrometry [3]. PC-046 was administered intravenously (IV), intraperitoneally (IP) or orally (PO) to compare bioavailability of different routes of administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AS-2 is a nonspecific kinesin inhibitor targeting several superfamily members including KHC, MPP1, MKLP1, RabK6, KIFC1, KIFC3, CENP-E, and Eg5 [64]. UA62784 has been reported to induce mitotic arrest and apoptosis in pancreatic carcinoma cell lines with high potency [65]. Initially, Henderson and co-workers described that UA62784, a fluorenone small molecule inhibits directly CENP-E microtubule-associated ATPase activity.…”
Section: Cenp-e Kinesin As a Therapeutic Targetmentioning
confidence: 98%